2018
DOI: 10.1186/s12889-018-6277-9
|View full text |Cite|
|
Sign up to set email alerts
|

Religion and Health: exploration of attitudes and health perceptions of faith healing users in urban Ghana

Abstract: BackgroundThe main aim of the study was to explore the attitudes and health perceptions of faith healing users in Kumasi Metropolis, Ghana. This has become necessary because faith healing practice is an important area but remains neglected in the health care literature. In an age when biowestern medicine is touted as the cure for most diseases, understanding how and why individuals seek alternative treatment, specifically faith healing modalities may help to develop more effective health care interventions.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
1
22
0
3
Order By: Relevance
“…In addition to promoting the public health guidelines for COVID-19, some of the musicians encouraged the use of prayer as well as verbally expelling the virus as methods of combating the disease. This is unsurprising because research has revealed that in Ghana, some people conceptualize the causes and cures of diseases through both biomedical and religious/spiritual means ( 43 , 44 , 56 ). As noted by Okyerefo and Fiavi ( 56 ), among Ghanaians, the religious/spiritual methods are viewed as complementary rather than challenging or competing with the biomedical models of healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting the public health guidelines for COVID-19, some of the musicians encouraged the use of prayer as well as verbally expelling the virus as methods of combating the disease. This is unsurprising because research has revealed that in Ghana, some people conceptualize the causes and cures of diseases through both biomedical and religious/spiritual means ( 43 , 44 , 56 ). As noted by Okyerefo and Fiavi ( 56 ), among Ghanaians, the religious/spiritual methods are viewed as complementary rather than challenging or competing with the biomedical models of healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The Islam faith users viewed faith healing in two ways, one is the application of Holy Quran for healing and the other one is consultation of Islamic leader [Malam] for instructions and prescriptions to deal with a health problem and they described faith healers as Muslim leaders who assist people in dealing with health challenges. [ 10 ] According to one article, the temple at Hanumanthapuram in Tamil Nadu is always packed with worshippers. Persons travel from different parts of India for long periods by various means including bullock cart to this rural part of Tamil Nadu as here the powerful Hindu deity, an incarnation of God Shiva purge evil spirits.…”
Section: Discussionmentioning
confidence: 99%
“…Religion and faith healing practice is an important aspect of the health care literature, especially when individuals start seeking an alternative treatment for their different maladies. Studies in West Africa have shown that faith healers served as the first port of call for malady curing and prevention (Peprah et al 2018). Followers and faith congregations perceived their health to have improved as their faith effectiveness increased.…”
Section: Religion and Healingmentioning
confidence: 99%
“…The use of the religious practice of faith healing in the diagnosis, for prevention and treatment of a plethora of health issues, and even social problems, dates back into antiquity (Thacore and Gupta 1978;Wardwell 1994;Kale 1995). The believers of faith healing and health, as well as faith healers, believe that their healing power comes from God through the Holy Spirit and/or ancestral spirits (Peprah et al 2018).…”
Section: Religion and Healingmentioning
confidence: 99%